The Discriminatory Impact of Social Media on Supplier and Customer Relationship Management in Manufacturing SMEs - Yong Dirgiatmo; Dwi Hascarya KB; Reza Rahardian; Miftachul Maarif (Inkubis : Jurnal Ekonomi dan Bisnis, 2026)
Background: Social media has become an essential part of human life, not only for information sharing and communication but also for effective business strategies. Objective: This study examines social media as a strategic tool for improving supplier relationship management (SRM) and customer relationship management (CRM) in manufacturing SMEs, focusing on how digital platforms foster trust, communication, and collaboration with business partners. Methods: This study involved 124 manufacturing SMEs located in the former Surakarta Residency area. After data collection, the relationships among the investigated variables were analyzed using a quantitative approach with structural equation modeling–partial least squares (SEM-PLS). Results: The results of this study show that social media does not necessarily contribute to improving supplier relationship management between small businesses and suppliers. The relationship between small businesses and customers is stronger than that between small businesses and suppliers, and no significant correlation was found between small businesses and suppliers in relation to customer satisfaction. These results are expected to make a positive contribution not only to small businesses, manufacturers, and manufacturing customers but also to local governments and academia. Conclusion: Although social media significantly improves CRM, its impact on SRM is limited. Customer satisfaction is significantly influenced by CRM rather than SRM, which positively affects the market performance of small businesses in the manufacturing industry. These findings highlight the need for small businesses to strategically utilize social media to improve business performance, especially in customer-facing contexts.